Genomic characterization of theBacillus cereussensu lato species: Backdrop to the evolution ofBacillus anthracis - Michael E. Zwick; Sandeep J. Joseph; Xavier Didelot; Peter E. Chen; Kimberly A. Bishop‐Lilly; Andrew C. Stewart; Kristin M. Willner; Nichole Nolan; Shannon M. Lentz; Maureen K. Thomason; Shanmuga Sozhamannan; Alfred Mateczun; et al. (2012)
The key genes required for Bacillus anthracis to cause anthrax have been acquired recently by horizontal gene transfer. To understand the genetic background for the evolution of B. anthracis virulence, we obtained high-redundancy genome sequences of 45 strains of the Bacillus cereus sensu lato (s.l.) species that were chosen for their genetic diversity within the species based on the existing multilocus sequence typing scheme. From the resulting data, we called more than 324,000 new genes representing more than 12,333 new gene families for this group. The core genome size for the B. cereus s.l. group was ∼1750 genes, with another 2150 genes found in almost every genome constituting the extended core. There was a paucity of genes specific and conserved in any clade. We found no evidence of recent large-scale gene loss in B. anthracis or for unusual accumulation of nonsynonymous DNA substitutions in the chromosome; however, several B. cereus genomes isolated from soil and not previously associated with human disease were degraded to various degrees. Although B. anthracis has undergone an ecological shift within the species, its chromosome does not appear to be exceptional on a macroscopic scale compared with close relatives.